ANALYSIS OF DEASES IN ELDERLY AND SENILE PERSONS, AFFECTING ACTIVE WORK ACTIVITY - Bokijonov , Farrukh Azizjon ogli (Innovative Development in Educational Activities, 2024)
Elderly people are a rapidly growing socio-demographic group, constituting a fifth of the country’s population, and by 2025 the number of people over 60 years of age will exceed one billion, which will account for 16% of the total population of our planet. In this regard, the problem of maintaining the quality of life of older people arises. The health status and morbidity patterns of older people differ significantly from those in other age groups. In this regard, the problem of health of elderly and senile people becomes relevant both for the Republic of Uzbekistan and for many countries of the world. Among the factors that determine public health, lifestyle factors and the availability of medical and social care play an important role.